2014
DOI: 10.4238/2014.august.26.4
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting of popcorn hybrids for resistance to fall armyworm

Abstract: ABSTRACT. The fall armyworm, Spodoptera frugiperda, is the pest that causes the greatest economic losses for both common corn and popcorn crops, and the use of resistant plant genotypes is an important tool for integrated pest management. The goal of the present study was to evaluate the damage caused by S. frugiperda on single-cross popcorn hybrids under field conditions with natural infestation as well as to study the effect of 11 popcorn hybrids on the S. frugiperda life cycle under laboratory conditions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Biological and chemical methods are strategies to control FAW, however, plant resistance is especially effective in tropical regions where there is a necessity to reduce environmental damages caused by misuse of pesticides (Cunha et al 2008;Crubelati-Mulati et al 2014). Although transgenic is a control alternative of great importance currently, as it facilitates crop management and reduces the use of highly toxic insecticides, studies have shown that FAW evolved resistance to Cry1F-maize (Farias et al 2014) and CryAb-maize in Brazil (Omoto et al 2016).…”
Section: Multivariate Analysis Reveals Key Traits Of Fall Armyworm Resistance In Tropical Popcorn Genotypes Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological and chemical methods are strategies to control FAW, however, plant resistance is especially effective in tropical regions where there is a necessity to reduce environmental damages caused by misuse of pesticides (Cunha et al 2008;Crubelati-Mulati et al 2014). Although transgenic is a control alternative of great importance currently, as it facilitates crop management and reduces the use of highly toxic insecticides, studies have shown that FAW evolved resistance to Cry1F-maize (Farias et al 2014) and CryAb-maize in Brazil (Omoto et al 2016).…”
Section: Multivariate Analysis Reveals Key Traits Of Fall Armyworm Resistance In Tropical Popcorn Genotypes Introductionmentioning
confidence: 99%
“…In addition, the work emphasizes that tropical germplasm is an important source of resistance to fall armyworm and ear armyworm in maize (Ni et al 2014). Although these studies clarify that genotypes can present resistance to FAW, few studies have been carried out to analyse popcorn genotypes (Crubelati-Mulati et al 2014;Oliveira et al 2018).…”
Section: Multivariate Analysis Reveals Key Traits Of Fall Armyworm Resistance In Tropical Popcorn Genotypes Introductionmentioning
confidence: 99%